Analysis of Defect Event Quantity Using Priority-Cost Failure Mode, Effect, And Criticality Analysis (PC-FMECA) Method (Case Study: Smoothmill Facility PT. Ebako Nusantara) - Ranintia Adhi Citra Pramesti; Bambang Purwanggono; Arfan Bakhtiar (Program Studi Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2016)
FMEA (Failure Mode and Effects Analysis) is a method to identify potential failure modes of a process or product, which has been used since 1950 inside an aviation control system. To implement more efficient improvement of FMEA, criticality analysis was then added into every failure mode, termed Failure Mode, Effects, and Criticality Analysis (FMECA). However, those methods are yet to integrate cost variable, which are essential in the rapid growth of manufacturing industries. Priority-Cost FMECA (PC-FMECA) emerged to reach such objective. PT. Ebako Nusantara is a high-end furniture manufacturing with several steps of production. Interview with QC Department and Defect Event Finding Data in October 2015 portrayed Smoothmill Facility as the area responsible for the largest defect event total in October 2015, which are 32,78%. This research is done to investigate the failures occurring during production so that defect event could be reduced, if not eliminated. This research uses PC-FMECA method, which takes profitability of action into account. In this method, the New RPN is calculated with the adoption of AHP technique, where profitability values are then formulated. Criticality matrices are drawn using priority-profitability diagram to formulate priority of failure. Upon this method, the recommendations are then customized to not exceed the budget of the company.